STORYLINE DEPICTION OF TRANSGENDER ISSUES IN PAKISTANI DRAMAS - saima waheed, saima waheed; waheed, Saima; Maria Naeem; sarosh bajwa; Sana Khushi (Journal of Peace, Development and Communication, 2021)
In the study entitled, “Storyline Depiction of Transgender Issues in Pakistani Dramas”. Several studies showed the power to influence behaviors and perceptions through scripted entertainment; fewer studied the effects of television representation on attitudes towards minority class. Latest study is one of the first to investigate how entertainment storytelling's portrayal transgender people changed the perceptions of audiences towards transgender people. Study analyzed the effect of exposure to a TV storyline on “Khuda Mera Bhai” and “Alif Allah Aur Insan” (ARY Digital & HUM TV) and complementary effects of screening other TV series featuring transgender individuals. Researcher was done content analysis and constructed a coding sheet regarding transgender issues which highlighted in these two selected dramas of two different channels. This study analyzed the effect of exposure to a TV storyline on “Khuda Mera Bhai” and “Alif Allah Aur Insan” (ARY Digital & HUM TV) and complementary effects of screening other TV series featuring transgender individuals. Researcher has done content analysis and constructed a coding sheet regarding transgender issues which highlighted in these two selected dramas of two different channels. After watching all relevant episodes of both dramas, coders had filled coding sheet given by researcher. Content Analysis disclosed the exposure of both selected dramas Khuda Mera Bhi hai and Alif Allah Aur Insan.Depicting the storylines of transgender individuals were affiliated with more supportive attitudes towards transgender characters and their issues. Attitudes of more conservative TV audience became more and more positive as they saw more media portrayals of transgender individuals. The findings highlighted the potential for entertainment content to influence attitudes toward minority groups.